Relationships between students' perceived team learning experiences, team performances, and social abilities in a blended course setting - Turel, Yalin Kilic (Elsevier Science Inc, 2016)
The main purpose of this study is to examine relationships between the social abilities, perceived team learning, and the performances of students in a blended learning setting. The participants, 82 undergraduate students, worked in small teams on a research method task over one semester. The instruments used for this study included a five-factor social ability scale and a one-dimensional perceived collaborative learning scale. The results showed moderate significant relationships between students' perceived team learning scores and students' peer social presence scores as well as weaker relationships between team learning and two social ability sub scales, written communication skills and instructor social presence. There appears to be an important effect of peer social presence that is linked to learning and performance. Using a blended learning model may have an important impact on increasing social interaction and learning with a team learning approach thereby helping students undertake comprehensive tasks and increase student learning. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Social ability; Team learning; Blended learning; Social presence; Collaborative learning